Pengaruh Pengaruh Pembangunan Sektor Keuangan dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Provinsi Riau - Azis, Andika Zaqrial; Yulyanti, Sinta (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of financial sector development and economic growth on poverty levels in Riau Province. Financial sector development is measured through the ratio of credit to Gross Regional Domestic Product (GRDP), while economic growth is measured using the real GRDP growth rate. The data used are annual secondary data for the 2013–2023 period obtained from official publications of Statistics Indonesia (BPS). The analysis was conducted using multiple linear regression with a quantitative approach. The results show that financial sector development has a negative and significant effect on poverty levels, indicating that increased credit distribution helps reduce poverty in Riau Province. Economic growth also has a negative and significant effect on poverty levels, suggesting that improved regional economic performance contributes to enhancing community welfare. Thus, strengthening the financial sector and regional economic activities is an effective strategy to reduce poverty levels in Riau Province.